2022
DOI: 10.1021/acs.jpcc.2c01459
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Spatial Resolution Cross-Disjoint Mortise-Confined Solid-State Nanopores with an Ultrathin Middle Layer

Abstract: Nanopore single-molecule technology, especially DNA/RNA sequencing based on nanopores, requires a high spatial resolution. In this paper, we theoretically studied the spatial resolution of the cross-disjoint mortise-confined solid-state nanopore (CDM-nanopore) structure that is formed by two perpendicular and disjoint nanochannels and a middle nanopore. When the thickness of the middle layer (nanopore) is 0 nm (i.e., the zero-depth interfacial nanopore), 0.6 nm, and 1 nm, the geometric resolution (δ z ) is 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…They reported that these nanopores possess superior mechanical qualities and an impressively low noise level, making them potentially valuable for sensitive detection applications . Furthermore, we also proposed cross-disjoint mortise-confined nanopores based on interfacial nanopores as a means of further improving resolution …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…They reported that these nanopores possess superior mechanical qualities and an impressively low noise level, making them potentially valuable for sensitive detection applications . Furthermore, we also proposed cross-disjoint mortise-confined nanopores based on interfacial nanopores as a means of further improving resolution …”
Section: Introductionmentioning
confidence: 89%
“…27 Furthermore, we also proposed crossdisjoint mortise-confined nanopores based on interfacial nanopores as a means of further improving resolution. 37 Despite the notable achievements in this field, understanding the fundamental mechanisms governing ion transport and associated processes in zero-depth interfacial nanopores remains a critical issue that requires further investigation. The study of ion transport properties is highly important for current nanofluidic applications, 38−40 and numerous studies have been conducted in the area of modeling ion transport to understand the fundamental mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%